PERAN GURU DALAM KONSTRUKSI BUDAYA RELIGIUS SEKOLAH MELALUI PRAKTIK KEAGAMAAN - Izza, Rohmatul; Ali Rohmad, Muhammad; Syarif, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Amid the tide of modernization that often erodes the spiritual values of the younger generation, madrasah are called to be more than institutions for transmitting religious knowledge they must become living spaces where religious character is continuously shaped, with teachers as key actors who cultivate students' habits into an enduring culture. This study aims to describe the role of teachers in building a school's religious culture and to analyze its construction process using Peter L. Berger and Thomas Luckmann's social construction theory, combined with B. F. Skinner's behavioristic theory to explain how religious behavior is formed through habituation and reinforcement. Employing a qualitative case study approach, data were gathered through observation, interviews, and documentation, analyzed using the Miles, Huberman, and Creswell interactive model, with validity ensured through source and technique triangulation. The findings show that religious culture is formed through two complementary processes: socially, it is constructed through the synergy of school principals, teachers, parents, students, and the pesantren environment via the stages of externalization, objectivation, and internalization; behaviorally, students' religious habits are shaped through repeated stimulus and reinforcement provided by teachers in practices such as communal prayer, congregational worship, istighosah, and tahlil. Teachers perform multidimensional roles as role models, motivators, mentors, facilitators, and agents of school culture, so that religious behavior first shaped through habituation develops into a culture embraced and sustained by the entire school community. This study affirms that social construction theory and behavioristic theory complement one another in explaining how religious culture is formed not as an instant outcome, but as the fruit of collective commitment and a consistent, sustained process of habituation.